En la elaboración del plan de cierre por parte de las concesionarias mineras, se debe incluir la participación ciudadana como un derecho constitucional - LOPEZ CARRIEL, DENISSE MARTHA (2014)
The need to include citizen participation in the development of the closure plan of mining operations in conjunction with the mining company is a topic of great interest because, it generates a series of negative consequences to be allowed to be the only company to develop the above mentioned plan, without taking into account the needs of communities affected by mining activity against this infringement of their rights and protected by the rules of the Constitution. Being a transcendental subject, it is important to note that the participation of communities in conjunction with the mining company would create a number of positive strategies that benefit and minimize the impacts caused by mining left, constituting a guarantee of respect faithful fulfillment of the rights that protect it and laws. After thorough research and search for important aspects obtained from different literature sources, it has been found that have and still are a number of cases where the rights not only of individuals but of the environment (environment are violated in where they live). The fact that the law requires mining companies to the development of the closure plan of mining operations is not sufficient basis for setting aside the right of communities to express and assert their rights, nor is it enough to ensure the recovery and rehabilitation of the affected areas. Since it is essential that the affected communities are direct participants because they are the ones who really know as the place was concerned, more than enough reasons why it is necessary to propose an amendment to Article 85 of the Mining Act, in left regarding the development of the closure plan of the mining activity is the active participation of the community in order that effective impartial and expeditious protection of the rights stipulated in the Constitution guaranteeing equal without discrimination whatsoever.